EKSPLIKASI KIRKPATRICK LEVEL 1 DAN 2 PADA PELATIHAN JARAK JAUH DI BALAI DIKLAT KEAGAMAAN BANDUNG - Nabilah, Syifa; Juniarahman, Nur Azizah; Purnomo, Purnomo (Tatar Pasundan: Jurnal Diklat Keagamaan, 2023)
The objective of this study is to conduct an evaluative analysis of the Religious Harmony Distance Training Batch III using the Kirkpatrick evaluation methodology. The training was conducted by the Bandung Religious Training Center, and the assessment will focus on the reaction and learning levels. The employed research methodology entails a descriptive approach that incorporates quantitative techniques. The study's sample consisted of all individuals who had participated in the third batch of the training program. Data for the study was obtained via questionnaires. The findings of this study indicate that the Kirkpatrick level 1 reaction model demonstrated trainees' satisfaction and positive response towards the training implementation. Additionally, at level 2, the learning outcomes effectively met the training objectives. Consequently, the application of the Kirkpatrick model at the reaction and learning levels successfully addressed issues in the third batch, yielding positive outcomes.Â Keywords: Evaluation; Religious Harmony Training; Kirkpatrick Model